Increased expression of kidney injury molecule-1 and matrix metalloproteinase-3 in severe Plasmodium falciparum malaria with acute kidney injury - Punsawad, Chuchard (Int J Clin Exp Pathol, 2017)
Kidney injury molecule-1 (KIM-1) is a specific histological biomarker for diagnosing early acute kidney injury which is markedly up-regulated in the proximal tubular cells in acute and chronic tubular injury. KIM-1 expression is poorly defined in the renal tubules of malaria patients. This present study aimed to determine KIM-1 expression as a specific biomarker for acute tubular damage and to identify matrix metalloproteinase-3 (MMP-3) as a mediator for KIM-1 shedding. Paraffin-embedded kidney tissues from autopsies of malaria patients were obtained from the Department of Tropical Pathology, Faculty of Tropical Medicine, Mahidol University, Thailand. The kidney tissues were divided into 2 groups: those with acute kidney injury (AKI) (n = 10 cases) and those with non-AKI (n = 10 cases). Ten normal kidney tissues were used as a control group. The expression of KIM-1 and MMP-3 was examined by immunohistochemical staining. KIM-1 and MMP-3 expressions were strongly expressed in the proximal tubular cells in all kidney tissues from severe Plasmodium falciparum malaria with histological changes showing acute tubular damage. The mean intensity and total score of KIM-1 and MMP-3 expressions were significantly increased in proximal tubules of AKI group compared to non-AKI and control groups (all P < 0.001). There was a significant positive correlation of total score of KIM-1 expression and the parameters of kidney function for AKI, including serum creatinine (Cr) and blood urea nitrogen (BUN). In addition, strong positive correlations were found between total score of KIM-1 expression and proximal tubular necrosis and MMP-3 expression. The study supports the potential role of KIM-1 as a specific biomarker for renal proximal tubular damage in malarial AKI, and indicates that the process of KIM-1 shedding might be stimulated by MMP-3.